Biohydrogen production from rotten orange with immobilized mixed culture: Effect of immobilization media for various composition of substrates - Damayanti, Astrilia; Department of Chemical Engineering, Faculty of Engineering, Gadjah Mada University, Jl. Grafika No. 2, Kampus UGM, Yogyakarta 55281; Sarto; Syamsiah, Siti; Sediawan, Wahyudi B. (AIP conference proceedings, 2015)
Enriched–immobilized mixed culture was utilized to produce biohydrogen in mesophilic condition under anaerobic condition using rotten orange as substrate. The process was conducted in batch reactors for 100 hours. Microbial cultures from three different sources were subject to a series of enrichment and immobilized in two different types of media, i.e. calcium alginate (CA, 2%) and mixture of alginate and activated carbon (CAC, 1:1). The performance of immobilized culture in each media was tested for biohydrogen production using four different substrate compositions, namely orange meat (OM), orange meat added with peel (OMP), orange meat added with limonene (OML), and mixture of orange meat and peel added with limonene (OMPL). The results show that, with immobilized culture in CA, the variation of substrate composition gave significant effect on the production of biohydrogen. The highest production of biohydrogen was detected for substrate containing only orange meet, i.e. 2.5%, which was about 3-5 times higher than biohydrogen production from other compositions of substrate. The use of immobilized culture in CAC in general has increased the hydrogen production by 2-7 times depending on the composition of substrate, i.e. 5.4%, 4.8%, 5.1%, and 4.4% for OM, OMP, OML, and OMPL, respectively. The addition of activated carbon has eliminated the effect of inhibitory compounds in the substrate. The major soluble metabolites were acetic acid, propionic acid, and butyric acid.